Exploring constraints in business travel for disabled workers: An ecological systems perspective - Karl, Marion; Pegg, Shane; Harpur, Paul (Disability & society, 2024)
It is reasonable to expect that travel systems at the workplace would consistently support disabled workers to travel for work in a manner consistent with their needs. Yet, insufficient travel support, systemic bias and discrimination are often the lived experience of disabled workers. To date, research has predominantly focused on leisure travel and disability. Applying an ecological systems theoretical frame, this study investigated how disabled workers in the higher education sector negotiate travel constraints during the organisation and experience of work-related travel. A qualitative research approach was used to understand and improve work-related travel for disabled workers. Findings revealed that disabled workers are regularly forced to negotiate layers of travel constraints related to their personal circumstances and embedded in an interacting environmental system comprising their private life, workplace and broader society. Recommendations are made for a work-travel system that is more inclusive of all workers.